CRITICAL APPROACHES TO HERITAGE FOR DEVELOPMENT - Cross, Charlotte; Giblin, John (Rethinking development, 2023)
This book investigates the relationship between heritage and development from the global visions articulated by UNESCO and the SDGs to local activism, livelihood innovations and political strategies employed in diverse countries of the Global South. In recent years, as culturally informed approaches to international development have become increasingly important, engaging with heritage has been seen as a way to draw on practices and meanings from the past to help build future development. This book gathers researchers and practitioners from across disciplines to address important themes such as health, the environment, sustainability, peace, security, tourism and economic growth. In doing so, the book asks us to consider whose past and whose future is ultimately at stake in efforts to use heritage for development. Key topics explored include histories and legacies of colonialism and calls for decolonisation, and related questions of expertise, ownership, and agency. Students, practitioners and researchers from across the broad areas of history, heritage, education, archaeology, geography, and development studies will find this book an invaluable guide to dynamic and contested understandings of heritage and development and the relationship between them.